Morphological Effect of CNT/TiO2 Nanocomposite Photoelectrodes Dye-Sensitized Solar Cell on Photovoltaic Performance with Various Annealing Temperatures - Mohd Zikri Razali; Huda Abdullah; Izamarlina Asaahari (International Journal of Photoenergy)
This research focused on the fabrication of dye-sensitized solar cell based on a photoanode of carbon nanotube/titanium dioxide (CNT/TiO2) nanocomposite photoanode synthesized through acid-catalyzed sol-gel method. The results show the improvement of the chemical and electrical properties of the solar cells annealed at different temperatures. The CNT/TiO2 colloidal solution was synthesized using titanium tetraisopropoxide and CNT/2-propanol solution. The thin films were doctor-bladed on a fluorine tin oxide glass before being annealed at 550, 650, and 750°C. The field emission scanning electron microscopy morphological images show that the thin films were homogenously distributed and maintained their spherical structures. The X-ray diffraction patterns show that the films consisted of anatase and rutile phases with large crystallite sizes due to temperature increment. The atomic force microscopy analysis presents the thin film roughness in terms of root mean square roughness. The photovoltaic performance was analyzed using IV curve and electrochemical impedance spectroscopy (EIS). The thin films annealed at 750°C had the highest energy conversion efficiency at 5.23%. The EIS analysis estimated the values of the effective electron lifetime (τeff), effective electron diffusion coefficient, effective electron diffusion (Ln), and effective recombination rate constant (keff). A large τeff, small keff, and longer Ln can improve photovoltaic performance efficiency.